Resin composition and stampable sheet

JP2025034186APending Publication Date: 2025-03-13MITSUBISHI CHEM ADVANCED MATERIALS JAPAN LTD

Patent Information

Application Number
JP2023140413
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、成形した際に、優れた電磁波遮蔽性を有し、かつ加工性に優れる樹脂組成物及び該樹脂組成物を用いたスタンパブルシートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034186000001
    Figure 2025034186000001
Patent Text Reader

Abstract

To provide a resin composition which has excellent electromagnetic wave shielding property when being formed, and is excellent in workability, and a stampable sheet using the resin composition.SOLUTION: There are provided a resin composition which contains a thermoplastic resin (A), a phosphorus flame retardant (B), coke powder and / or carbon fiber (C), and a dispersant (D), wherein the dispersant (D) contains an acid-modified polyolefin-based resin; and a stampable sheet using the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a stampable sheet containing the resin composition. [Background technology]

[0002] In recent years, research and development of electric and hybrid vehicles has been promoted as part of environmental measures, and the development of high-energy density batteries and weight reduction are being actively promoted in order to improve the driving range. Such high-energy density batteries are at risk of catching fire in the event of an accident, so as a safety measure for passengers, the housing material must have high flame retardancy, and therefore, in many cases, metal materials such as iron are used in combination with fire-resistant materials. However, metal materials have the drawback of being heavy, and when fire-resistant materials are used in combination, issues arise regarding workability and increased costs due to the increased number of parts. Therefore, attempts are being made to use resins, which have the potential to achieve both weight reduction and flame resistance. Currently, in order to create a sustainable society, emphasis is being placed on reducing carbon dioxide emissions and recyclability. Many thermosetting materials have high flame retardancy and are common as composite materials, but in terms of recyclability, thermoplastic resin materials are advantageous.

[0003] To address these issues, for example, Patent Document 1 proposes the addition of a brominated flame retardant or an antimony oxide compound to a carbon fiber reinforced polypropylene resin, but the additives used here have a problem with their persistence in the body. In response to this, in consideration of bioretention, a flame-retardant polyolefin-based composition in which a (poly)phosphate compound is contained in a polyolefin-based resin is proposed as a technology for making a polypropylene-based resin flame-retardant. However, the resin composition described therein has a problem in that the dispersibility of the phosphorus-based flame retardant is poor. In addition, Patent Document 3 proposes a flame-retardant resin composition containing long glass fibers and a phosphate compound in a polypropylene resin. However, as in Patent Document 2, it is necessary to contain a large amount of a phosphorus-based flame retardant, and there is a problem with the dispersibility of the phosphorus-based flame retardant.

[0004] Meanwhile, in order to prevent effects on the human body and malfunction of electronic devices, etc., a conductive function is imparted to cover materials used in automobile parts, electronic devices, etc. to shield electromagnetic waves. Specifically, for example, a cover material used for an upper cover of a battery pack for an electric vehicle is formed using a metal plate or the like to shield electromagnetic waves emitted from the battery pack. On the other hand, in order to reduce the weight of automobiles, electronic devices, etc., there is a demand to use resins for such cover materials. Therefore, various resin molded products having electromagnetic wave shielding properties have been studied. For example, Patent Document 4 discloses a conductive resin composition in which coke powder and carbon-based flaky conductive filler (graphite) or metal-based flaky conductive filler are mixed in a predetermined weight ratio with a thermosetting or thermoplastic resin material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-62189 A [Patent Document 2] JP 2013-119575 A [Patent Document 3] JP 2011-88970 A [Patent Document 4] Japanese Patent Application Publication No. 6-251620 Summary of the Invention [Problem to be solved by the invention]

[0006] While resinification has the potential to achieve both lightweight and flame-resistant properties for high-energy density batteries, conventional technologies have many shortcomings. For example, there is a problem that the carbon fiber length in the carbon fiber reinforced polypropylene resin composition disclosed in Patent Document 1 does not provide sufficient strength and rigidity after stamp molding.

[0007] In addition, the resin compositions disclosed in Patent Documents 2 and 3 have poor dispersibility of the phosphorus-based flame retardant, and although flame retardancy can be obtained by adding a large amount of phosphorus-based flame retardant, there is a problem that the strength of the polypropylene-based resin is significantly reduced. In addition, when a stampable sheet material contains a large amount of flame retardant, molding defects (unfilled molding) are likely to occur during stamp molding, and there is a problem that the mechanical properties of the stampable sheet and the flowability during stamp molding cannot be maintained.

[0008] Furthermore, in the field of automobiles, technologies that use electromagnetic waves to sense distance, speed, and obstacles have been realized, and in order to achieve accurate sensing, it is necessary to block unnecessary electromagnetic waves with high precision.

[0009] Therefore, an object of the present invention is to provide a resin composition that has excellent electromagnetic wave shielding properties and excellent processability when molded, and a stampable sheet using the resin composition. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by a resin composition containing a thermoplastic resin, a phosphorus-based flame retardant, coke powder and / or carbon fiber, and a specific dispersant. The present invention was completed based on the above findings.

[0011] That is, the present invention relates to the following. [1] A resin composition comprising a thermoplastic resin (A), a phosphorus-based flame retardant (B), coke powder and / or carbon fiber (C), and a dispersant (D), wherein the dispersant (D) comprises an acid-modified polyolefin resin. [2] The resin composition according to the above [1], wherein the phosphorus-based flame retardant (B) contains a compound having a melamine structure or a piperazine structure. [3] The resin composition according to the above [1] or [2], wherein the phosphorus-based flame retardant (B) includes an intumescent flame retardant. [4] The resin composition according to any one of the above [1] to [3], wherein the dispersant (D) contains a copolymer of an α-olefin and an unsaturated carboxylic acid. [5] The resin composition according to the above [4], wherein the unsaturated carboxylic acid is maleic anhydride. [6] The resin composition according to any one of the above [1] to [5], wherein the thermoplastic resin (A) comprises a polypropylene resin. [7] A stampable sheet comprising the resin composition according to any one of [1] to [6] above and glass fibers. [8] The stampable sheet according to [7] above, comprising a mat formed by impregnating the glass fiber with the resin composition. [9] The stampable sheet according to the above [8], wherein the mat is a glass fiber mat produced by needle punching a swirl mat of continuous glass fibers, and impregnated with the resin composition. Effect of the Invention

[0012] According to the present invention, it is possible to provide a resin composition which, when molded, has excellent electromagnetic wave shielding properties and excellent processability, and a stampable sheet using the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the following embodiments, and can be modified in various ways within the scope of the present invention.

[0014] [Resin composition] The resin composition of the present invention (hereinafter, may be referred to as "the resin composition") contains a thermoplastic resin (A), a phosphorus-based flame retardant (B), coke powder and / or carbon fiber (C), and a dispersant (D).

[0015] <Thermoplastic resin (A)> The thermoplastic resin (A) is not particularly limited, and examples thereof include polyolefin resin, polycarbonate resin, polyester resin, acrylonitrile styrene resin, ABS resin, polyamide resin, modified polyphenylene oxide, etc. These may be used alone or in combination of two or more. For example, the thermoplastic resin (A) may be a composite resin of two or more of the above thermoplastic resins.

[0016] The polyolefin resin is not particularly limited, and may be any of the resins described below. The polyester resin is not particularly limited, and may be, for example, polybutylene terephthalate. The polyamide resin is not particularly limited, and may be, for example, nylon 66 or nylon 6. Among them, the present invention is particularly useful when the thermoplastic resin (A) is a polyolefin resin. In the present invention, the term "polyolefin resin" refers to a resin in which the proportion of olefin units or cycloolefin units is 90 mol % or more relative to 100 mol % of all structural units constituting the resin. The proportion of olefin units or cycloolefin units relative to 100 mol % of all structural units constituting the polyolefin resin is preferably 95 mol % or more, and particularly preferably 98 mol % or more.

[0017] Examples of polyolefin resins include α-olefin polymers such as polyethylene, polypropylene, polybutene, poly(3-methyl-1-butene), poly(3-methyl-1-pentene), and poly(4-methyl-1-pentene); α-olefin copolymers such as ethylene-propylene block or random copolymers, α-olefin-propylene block or random copolymers having 4 or more carbon atoms, ethylene-methyl(meth)acrylate copolymers, and ethylene-vinyl acetate copolymers; and cycloolefin polymers such as polycyclohexene and polycyclopentene.

[0018] Examples of polyethylene include low-density polyethylene, linear low-density polyethylene, and high-density polyethylene. Examples of polypropylene include isotactic polypropylene, syndiotactic polypropylene, hemiisotactic polypropylene, and stereoblock polypropylene. In the α-olefin-propylene block or random copolymer having 4 or more carbon atoms, examples of the α-olefin having 4 or more carbon atoms include butene, 3-methyl-1-butene, 3-methyl-1-pentene, and 4-methyl-1-pentene. These polyolefin resins may be used alone or in combination of two or more. The polyolefin resin preferably contains polypropylene. Polypropylene may be used in combination with other polyolefin resins. For example, as the polyolefin resin, a mixture of polypropylene with other α-olefin polymers such as ethylene-propylene block or random copolymers, and α-olefin-propylene block or random copolymers having 4 or more carbon atoms may be used.

[0019] The polyolefin resin is preferably composed mainly of polypropylene, and the proportion of polypropylene in 100% by mass of the polyolefin resin is preferably 50% by mass or more, and more preferably 60% by mass or more. From the viewpoint of flame retardancy, the polyolefin resin is particularly preferably polypropylene, that is, it is preferable that the thermoplastic resin (A) contains a polypropylene resin.

[0020] The melt mass flow rate (MFR) of the thermoplastic resin (A) is preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more, while it is preferably 80 g / 10 min or less, more preferably 60 g / 10 min or less. If the MFR of the thermoplastic resin (A) is the lower limit or more, the molding processability is better, and if it is the upper limit or less, the bending properties, tensile properties, chemical resistance properties, etc. are better. The preferable lower limit value and upper limit value can be appropriately combined.

[0021] The MFR of the thermoplastic resin (A) may be, for example, 0.1 g / 10 min or more and 80 g / 10 min or less, or 0.5 g / 10 min or more and 60 g / 10 min or more. The melt mass flow rate of the thermoplastic resin (A) is measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0022] The proportion of the thermoplastic resin (A) in the resin composition is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. On the other hand, it is preferably 85% by mass or less, more preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. If the proportion of the thermoplastic resin (A) is equal to or more than the lower limit, the inherent physical properties of the thermoplastic resin (A) are easily expressed, and if it is equal to or less than the upper limit, the flame retardancy is more excellent.

[0023] The proportion of the thermoplastic resin (A) in the present resin composition may be, for example, 20% by mass or more and 85% by mass or less, 30% by mass or more and 80% by mass or less, 40% by mass or more and 70% by mass or less, or 50% by mass or more and 60% by mass or less.

[0024] <Phosphorus-based flame retardants (B)> The phosphorus-based flame retardant (B) is a phosphorus compound, i.e., a compound containing a phosphorus atom in the molecule. The phosphorus-based flame retardant (B) exerts a flame retardant effect by forming char when the resin composition is burned. The phosphorus-based flame retardant (B) is preferred because it is non-remaining in living organisms and has excellent flame retardancy, and is also preferred from the environmental point of view because it does not contain halogens. The phosphorus-based flame retardant (B) may be a known one, and examples thereof include (poly)phosphates, (poly)phosphate esters, etc. Here, "(poly)phosphates" refers to phosphates or polyphosphates, and "(poly)phosphate esters" refers to phosphate esters or polyphosphate esters. The phosphorus-based flame retardant (B) is preferably a solid at 80°C.

[0025] From the viewpoint of flame retardancy, the phosphorus-based flame retardant (B) is preferably a (poly)phosphate, and the phosphorus-based flame retardant (B) preferably contains a compound having a melamine structure or a piperazine structure. Examples of (poly)phosphates include ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, piperazine orthophosphate, melamine pyrophosphate, piperazine pyrophosphate, melamine polyphosphate, melamine orthophosphate, calcium phosphate, and magnesium phosphate. In addition, in the above examples, compounds in which melamine or piperazine is replaced with other nitrogen compounds can be used in the same manner. Examples of other nitrogen compounds include N,N,N',N'-tetramethyldiaminomethane, ethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-diethylethylenediamine, 1,2-propanediamine, 1,3-propanediamine, tetramethyl Diamine, pentamethylenediamine, hexamethylenediamine, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, trans-2,5-dimethylpiperazine, 1,4-bis(2-aminoethyl)piperazine, 1,4-bis(3-aminopropyl)piperazine, acetoguanamine, benzoguanamine, acrylguanamine, 2,4-diamino-6-nonyl-1,3,5-triamine 2,4-diamino-6-hydroxy-1,3,5-triazine, 2-amino-4,6-dihydroxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-ethoxy-1,3,5-triazine, 2,4-diamino-6-propoxy-1,3,5-triazine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2,4-diamino-6-mercapto-1, Examples of such (poly)phosphates include 3,5-triazine, 2-amino-4,6-dimercapto-1,3,5-triazine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, melamine pyrophosphate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, 1,3-hexylenedimelamine, etc. These (poly)phosphates may be used alone or in combination of two or more.

[0026] The phosphorus-based flame retardant (B) is preferably a salt of (poly)phosphoric acid and a nitrogen compound (hereinafter, sometimes referred to as "compound (B1)"). Compound (B1) is an intumescent flame retardant, and will be described in detail later.

[0027] Commercially available phosphorus-based flame retardants (B) include Adeka STAB FP-2100J, FP-2200, and FP-2500S (manufactured by ADEKA CORPORATION).

[0028] (Intumescent flame retardant) The intumescent flame retardant forms a carbonized film when the resin composition is burned, and the carbonized film expands to form a surface expansion layer (intemescent). The formation of the surface expansion layer suppresses the diffusion of decomposition products and heat transfer, resulting in excellent flame retardancy. Examples of the nitrogen compound in the compound (B1) include ammonia, melamine, piperazine, and the other nitrogen compounds described above. Intumescent flame retardants are flame retardants that suppress the combustion of materials by forming a surface expansion layer (intemescent) that prevents the diffusion of radiant heat from the combustion source and combustion gases and smoke from the burning material to the outside. Therefore, intumescent flame retardants are preferred from the viewpoint of improving flame resistance.

[0029] Examples of the intumescent flame retardant include salts of (poly)phosphoric acid and nitrogen compounds, specifically ammonium salts and amine salts of (poly)phosphoric acid, such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, ammonium pyrophosphate, melamine pyrophosphate, and piperazine pyrophosphate. The flame retardants may be used alone or in combination of two or more.

[0030] The content of the phosphorus-based flame retardant (B) in the resin composition is not particularly limited, but is preferably in the range of 1 to 50% by mass. When it is 1% by mass or more, good flame retardancy can be imparted and good flame shielding properties can be obtained. On the other hand, when the phosphorus-based flame retardant (B) is 50% by mass or less, the thermoplastic resin (A) can be contained in a sufficient content ratio, so that the molding processability becomes better. From the above viewpoints, the content of the phosphorus-based flame retardant (B) in the resin composition is more preferably in the range of 5 to 40% by mass, and further preferably in the range of 10 to 35% by mass.

[0031] <Coke powder and / or carbon fiber (C)> The resin composition contains coke powder and / or carbon fiber as component (C). The coke powder and carbon fiber may be contained alone or in combination. By containing the coke powder and / or carbon fiber (C), excellent electromagnetic wave shielding properties can be obtained. Here, excellent electromagnetic wave shielding properties means that the shielding effect against electromagnetic waves of frequencies from 300kHz to 3MHz (more specifically, 1.7MHz) used for example in ship communications, medium wave broadcasting (AM radio), ship and aircraft beacons, amateur radio, etc. is 45dB or more (shielding rate 99%). The measured value of the electromagnetic wave shielding effect is the value measured according to the KEC method (a method for measuring the electromagnetic wave shielding effect developed by the KEC Kansai Electronics Industry Development Center, a general incorporated association).

[0032] (Coke powder) Coke powder is a pulverized particle of carbon material (coke) obtained by carbonizing coal or by coking (thermal polymerization) petroleum or coal-based heavy oil. This coke powder is a relatively inexpensive material compared to carbon black or artificial graphite. Coke powder also has electrical conductivity equivalent to that of carbon black and carbon fiber.

[0033] As the coke powder, generally available commercially available coke powder can be used, but from the viewpoint of improving electrical conductivity, pitch coke powder is preferable. This pitch coke powder is a graphitizable carbon material obtained by high-temperature firing of soft pitch (SOP) separated from coal tar, a by-product of carbonization (steaming) of coal, to remove volatile matters.

[0034] The shape of the coke powder may be, for example, spherical, elliptical, flaky, fibrous, dendritic, etc. As the coke powder, a single shape of coke powder may be used, or a combination of coke powders of different shapes may be used.

[0035] The volume average particle diameter (MV) of the coke powder is 1 μm or more, preferably 10 μm or more, from the viewpoint of improving electrical conductivity. Also, the volume average particle diameter of the coke powder is 500 μm or less, preferably 50 μm or less, from the viewpoint of improving moldability. In this specification, the volume average particle diameter refers to the volume-weighted average diameter measured by a laser diffraction / scattering method.

[0036] When coke powder is used as component (C), the content of the coke powder in the resin composition is 1% by mass or more, preferably 3% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, and particularly preferably 10% by mass or more, from the viewpoint of improving electrical conductivity. Also, the content of the coke powder is 40% by mass or less, preferably 30% by mass or less, and more preferably 20% by mass or less, from the viewpoint of improving moldability.

[0037] (Carbon Fiber) The carbon fibers that can be used include commercially available carbon fibers such as polyacrylonitrile (PAN-based), pitch-based, cellulose-based, vapor-grown carbon fibers using hydrocarbons, graphite fibers, etc. These carbon fibers may be used alone or in combination of two or more types.

[0038] From the viewpoint of improving electrical conductivity, the average fiber length (weight average fiber length) of the carbon fibers is preferably 0.5 mm or more, more preferably 1 mm or more, further preferably 2 mm or more, and particularly preferably 3 mm or more. From the viewpoint of improving moldability and mechanical properties, the average fiber length of the carbon fibers is preferably 25 mm or less, more preferably 10 mm or less. Among the carbon fibers, from the viewpoint of further improving electrical conductivity, long fiber carbon fibers having an average fiber length of 2 mm or more are preferred. In this specification, the average fiber length refers to the average fiber length measured by extracting 100 or more fibers from the molded article. Methods for extracting fibers include, for example, an incineration method.

[0039] The average fiber diameter of the carbon fibers is preferably 3 μm or more, more preferably 6 μm or more, from the viewpoint of improving electrical conductivity, and is preferably 12 μm or less, more preferably 10 μm or less, from the viewpoint of improving moldability and mechanical properties. In this specification, the average fiber diameter refers to the average diameter obtained by dividing the sum of the diameters of the monofilaments (monofilament diameters) constituting the fiber bundle by the number of monofilaments constituting the fiber bundle and averaging the result. The monofilament diameter refers to the average value of the maximum and minimum diameters of the cross section obtained when the monofilament is cut in a direction perpendicular to the fiber axis direction. The shape of the cross section of the fiber is not particularly limited, and may be a perfect circle or an ellipse. The outer periphery of the cross section of the fiber may be a wavy shape with irregularities. The height of the irregularities may be within about 10% of the monofilament diameter.

[0040] From the viewpoint of improving electrical conductivity and mechanical properties, the aspect ratio of the carbon fiber is preferably 3 or more, more preferably 70 or more, even more preferably 100 or more, still more preferably 300 or more, and particularly preferably 500 or more. From the viewpoint of improving moldability, the aspect ratio of the carbon fiber is preferably 1700 or less, more preferably 1000 or less, and even more preferably 600 or less. In this specification, the aspect ratio refers to the ratio of the length of the fiber in the longitudinal direction (fiber axis direction) to the length in the lateral direction perpendicular to the longitudinal direction. The aspect ratio refers to a value measured by a laser diffraction / scattering method.

[0041] When carbon fiber is used as component (C), the content of carbon fiber in the resin composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more from the viewpoint of improving electrical conductivity. Also, the content of carbon fiber is 10% by mass or less, preferably 7% by mass or less, and more preferably 5% by mass or less from the viewpoint of reducing the cost of the stampable sheet.

[0042] When carbon fiber is used alone as a conductive material, in order to ensure sufficient electromagnetic wave shielding properties (for example, 45 dB or more), it is preferable to add long fiber carbon fiber with a content of 2 mass% or more to the thermoplastic resin (A), and it is more preferable to add long fiber carbon fiber with a content of 3 mass% or more to the thermoplastic resin (A). On the other hand, if the carbon fiber content is increased, the fluidity of the thermoplastic resin (A) deteriorates, and wear of the cylinder and mold of the kneader increases, which may result in poor moldability. Furthermore, the cost of the stampable sheet may increase.

[0043] As mentioned above, coke powder and carbon fiber may be used as component (C), and when used in combination, excellent electromagnetic shielding properties are exhibited. The reason for this is believed to be due to the formation of a network of coke powder and carbon fiber dispersed in the thermoplastic resin (A), as described above. More specifically, the carbon fiber comes into contact with the coke powder that is separated from each other in the thermoplastic resin (A), forming a path through which electricity can pass. As a result, it is believed that the percolation phenomenon occurs, dramatically increasing the conductivity.

[0044] When coke powder and carbon fiber are used as component (C), the total content of the coke powder and carbon fiber in the resin composition is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and particularly preferably 15% by mass or more, from the viewpoint of improving electrical conductivity. Also, the total content of the coke powder and carbon fiber is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less, from the viewpoint of improving moldability and mechanical properties and reducing the cost of the stampable sheet used as an electromagnetic wave shielding material.

[0045] In addition, other conductive materials (optional components) than the coke powder and carbon fiber may be added to the resin composition as long as the effect of the present disclosure is not impaired. Examples of the other conductive materials include carbon black; metal fibers; metal fillers such as copper powder, silver powder, nickel powder, silver-coated copper powder, gold-coated copper powder, silver-coated nickel powder, and gold-coated nickel powder; and metal-coated resin fillers. These other conductive materials may be used alone or in combination of two or more. Among the other conductive materials, carbon black is preferred.

[0046] Examples of carbon black include acetylene black, gas black, oil black, naphthalene black, thermal black, furnace black, lamp black, channel black, roll black, disc black, and ketjen black, depending on the raw material and production method.

[0047] Furthermore, glass fibers may be added to the resin composition, which can further improve the mechanical properties and electrical conductivity of the molded article.

[0048] The type of glass fiber may be, for example, E glass, C glass, S glass, D glass, or other commercially available glass fiber. The form of the glass fiber is not particularly limited, and any glass fiber such as chopped strand, roving, yarn, glass wool, or the like may be used. These glass fibers may be used alone or in combination of two or more types.

[0049] <Dispersant (D)> The dispersant (D) has the function of dispersing the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) in the thermoplastic resin (A), and in the present invention, the dispersant (D) contains an acid-modified polyolefin resin. The acid-modified polyolefin resin is a polymer dispersant having a functional group. From the viewpoint of dispersion stability, preferred examples of the polymer dispersant include a polymer dispersant having a functional group such as a carboxyl group, a phosphoric acid group, or a sulfonic acid group, and in particular, a polymer dispersant having a carboxyl group. More specifically, a copolymer of α-olefin and unsaturated carboxylic acid is preferred. By using the dispersant, the dispersibility of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) can be improved, and the content of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) can be reduced. In addition, the improved dispersibility of the coke powder and / or carbon fiber (C) can result in improved electromagnetic wave shielding properties.

[0050] (copolymer of α-olefin and unsaturated carboxylic acid) In the "copolymer of α-olefin and unsaturated carboxylic acid" according to the present invention (hereinafter, sometimes referred to as "copolymer (D1)"), it is preferable that the proportion of α-olefin units in the total of 100 mol % of α-olefin units and unsaturated carboxylic acid units is 20 mol % or more and 80 mol % or less. In the copolymer (D1), the ratio of the α-olefin unit to the total amount of the α-olefin unit and the unsaturated carboxylic acid unit is more preferably 30 mol% or more, and more preferably 70 mol% or less. If the ratio of the α-olefin is above the lower limit, the compatibility with the thermoplastic resin (A) such as a polyolefin resin is more excellent, and if it is below the upper limit, the compatibility with the phosphorus-based flame retardant (B) can be improved. As a result, the dispersibility of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) can be made sufficient.

[0051] In the copolymer (D1), the α-olefin is preferably an α-olefin having 5 or more carbon atoms, and more preferably an α-olefin having 10 to 80 carbon atoms. If the α-olefin has 5 or more carbon atoms, compatibility with the thermoplastic resin (A) tends to be better, and if it has 80 or less carbon atoms, it is advantageous in terms of raw material costs. From the above viewpoints, the α-olefin more preferably has 12 to 70 carbon atoms, and particularly preferably has 18 to 60 carbon atoms.

[0052] In the copolymer (D1), examples of the unsaturated carboxylic acid include (meth)acrylic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, glutaconic acid, norbornane-5-ene-2,3-dicarboxylic acid, and esters, anhydrides, imides, etc. of these unsaturated carboxylic acids. Note that "(meth)acrylic acid" refers to acrylic acid or methacrylic acid. Specific examples of the ester, anhydride or imide of an unsaturated carboxylic acid include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and glycidyl (meth)acrylate; dicarboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride; and maleimide compounds such as maleimide, N-ethylmaleimide, and N-phenylmaleimide. These may be used alone or in combination of two or more. Among the above, esters and dicarboxylic anhydrides are preferred from the viewpoint of copolymerization reactivity, and among these, dicarboxylic anhydrides are preferred from the viewpoint of compatibility with the phosphorus-based flame retardant (B), with maleic anhydride being particularly preferred.

[0053] The weight average molecular weight of the copolymer (D1) is preferably at least 2,000, more preferably at least 3,000, and on the other hand, is preferably at most 50,000, more preferably at most 30,000. When the weight average molecular weight of the copolymer (D1) is within the above range, the dispersibility of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) is improved. The weight average molecular weight of the copolymer (D1) is a value calculated as standard polystyrene by dissolving the copolymer (D1) in tetrahydrofuran (THF) and measuring the resultant by gel permeation chromatography.

[0054] Commercially available products of the copolymer (D1) include Lycorb CE2 (manufactured by Clariant Japan KK) and Diacaluna 30M (manufactured by Mitsubishi Chemical Corporation).

[0055] The content of the dispersant (D) in the resin composition is in the range of more than 0 parts by mass and not more than 25 parts by mass, preferably in the range of 0.01 to 10 parts by mass, relative to 100 parts by mass of the total amount of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C). The stampable sheet, which is one embodiment of a molded article formed from the resin composition, is uniformly dispersed in the glass fibers constituting the stampable sheet with the thermoplastic resin (A) as the matrix resin, and the flame-resistant properties of the stampable sheet can be significantly improved. Although the detailed mechanism is unclear, when the phosphorus-based flame retardant (B) is uniformly dispersed in the resin between the glass fibers, the char formed by the phosphorus-based flame retardant (B) coming into contact with flame is fixed in the gaps between the glass fibers. Furthermore, the size of the char formed by expansion upon contact with flame is restricted by the gaps between the glass fibers, and the size of the char formed becomes uniform. It is believed that the combination of the char fixing effect of the inorganic fibers and the uniformity of the char size results in the formation of dense char, which significantly improves the flame-resistant properties of the stampable sheet. In addition, it is believed that the dispersibility of the coke powder and / or carbon fiber (C) in the thermoplastic resin (A) is improved, and therefore the electromagnetic wave shielding property of the stampable sheet formed from the resin composition is improved.

[0056] For the above reasons, if the content of the dispersant (D) is 0, the dispersibility of the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) will be insufficient, and the stampable sheet, which is one embodiment of the molded body, will not be able to be imparted with sufficient flame-proofing properties and electromagnetic wave shielding properties. On the other hand, if it is 25 parts by mass or less, sufficient physical properties of the stampable sheet, which is one embodiment of the molded product, are ensured. From the above viewpoints, the content of the dispersant (D) is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.5 parts by mass or more, and particularly preferably 1 part by mass or more. On the other hand, the upper limit is more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less.

[0057] In addition, the ratio of the dispersant (D) to the total of 100 parts by mass of the thermoplastic resin (A), the phosphorus-based flame retardant (B), and the coke powder and / or carbon fiber (C) is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more. On the other hand, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1 part by mass or less. If the ratio of the dispersant (D) is equal to or more than the lower limit, the phosphorus-based flame retardant (B) and the coke powder and / or carbon fiber (C) are more favorably dispersed, and the flame-proofing property, electromagnetic wave shielding property, and other physical properties as a stampable sheet of the obtained stampable sheet, and the appearance of the molded product obtained from the stampable sheet are more favorable. If the ratio of the dispersant (D) is equal to or less than the upper limit, the influence of the dispersant (D) on the flame-proofing property of the stampable sheet can be more suppressed, and the electromagnetic wave shielding property can be more improved.

[0058] [Molded body] The molded article formed from the present resin composition is not particularly limited, and may have various shapes such as a resin plate, sheet, film, cable, or irregular shape. The molded article can be obtained by molding the resin composition. The molding method is not particularly limited, and examples of the molding method include extrusion, calendaring, injection molding, rolling, compression molding, blow molding, stamping molding, and the like. The molded article is preferably a stampable sheet as described below.

[0059] [Stampable sheet] The stampable sheet of the present invention contains the above-mentioned resin composition and glass fibers. Glass fibers are suitable in terms of flame resistance and processability. In addition to glass fibers, other inorganic fibers having different melting temperatures may be used in combination. The other inorganic fibers are preferably a combination of one or more inorganic fibers selected from the group consisting of alumina fibers, silica fibers, alkaline earth silicate fibers (biosoluble), and carbon fibers. Incidentally, by containing two or more types of inorganic fibers having different melting temperatures, it is possible to effectively prevent the deterioration of the flame-blocking property.

[0060] (Glass fiber) The glass fibers may be, for example, long fibers having an average fiber length of 30 mm or more, or may be fibers having a short average fiber length (chopped strands). From the standpoint of flame retardancy, rigidity, impact resistance, etc., it is preferable to use glass fibers having a long average fiber length. More specifically, the average fiber length is preferably 5 mm or more. When the average fiber length is 5 mm or more, the stampable sheet has good strength and impact resistance. From the above viewpoints, the average fiber length of the glass fiber is preferably 5 mm or more, and more preferably 30 mm or more. There is no particular upper limit to the average fiber length of glass fibers, and for example, when using pellets produced by the pultrusion method using glass fibers, the length of the pellets is the fiber length of the glass fibers, which is a maximum of about 20 mm. In addition, in the case of a swirl mat system using long glass fibers, the length of the glass fibers in the roving used for production is the maximum fiber length, which can be as long as 17,000 m (17 km), but when cut to fit the size of the stampable sheet, the cut length is the maximum fiber length.

[0061] The average fiber diameter of the glass fibers is preferably in the range of 9 to 25 μm. When the average fiber diameter is 9 μm or more, the stampable sheet has sufficient rigidity and impact resistance, while when the average fiber diameter is 25 μm or less, the stampable sheet has good strength. From the above viewpoints, the average fiber diameter of the glass fibers is more preferably in the range of 10 to 15 μm. The fiber diameter of the glass fibers can be measured using a scanning electron microscope or the like, and the average fiber diameter can be obtained by, for example, measuring the fiber diameters of 10 randomly selected fibers and calculating the average value. The fiber length can be measured using a ruler, calipers, or the like from an image enlarged by a microscope or the like as necessary, and the average fiber length can be obtained by, for example, measuring the fiber lengths of 10 randomly selected fibers and calculating the average value.

[0062] The material of the glass fiber used in the present invention is not particularly limited, and may be any of alkali-free glass, low-alkali glass, and alkali-containing glass, and various compositions that have conventionally been used as glass fibers can be used. The glass fibers are preferably prepared by cutting strand bundles to a specified length, arranging them in a swirl shape, bonding them together using needle punching, dispersing the resulting swirl mat in random directions, laminating them to a uniform thickness, and then adding a binder to form a mat.

[0063] The glass fiber content in the stampable sheet of the present invention is preferably 1 to 80% by mass. When the glass fiber content is 1% by mass or more, the stampable sheet has sufficient strength, rigidity, and impact resistance. On the other hand, when the glass fiber content is 80% by mass or less, the stampable sheet is easy to manufacture and process. In addition, when the glass fiber content is 80% by mass or less, the specific gravity of the stampable sheet is reduced, and thus a weight reduction effect as a metal substitute is obtained. From the above viewpoints, the glass fiber content in the stampable sheet is more preferably 3 to 60 mass %, further preferably 10 to 50 mass %, and particularly preferably 30 to 45 mass %.

[0064] <Optional addition ingredients> In addition to the above components, the stampable sheet of the present invention may contain any additive components for the purpose of further improving the effects of the invention or imparting other effects, as long as the effects of the invention are not significantly impaired. Specific examples of such additives include colorants such as pigments, light stabilizers such as hindered amines, ultraviolet absorbers such as benzotriazoles, nucleating agents such as sorbitol, antioxidants such as phenols and phosphorus, antistatic agents such as nonionic surfactants, neutralizing agents such as inorganic compounds, antibacterial and antifungal agents such as thiazoles, flame retardants and flame retardant assistants such as halogen compounds and lignophenols, plasticizers, dispersants such as organic metal salts, lubricants such as fatty acid amides, metal deactivators such as nitrogen compounds, polyolefin resins other than the polypropylene resins, thermoplastic resins such as polyamide resins and polyester resins, and elastomers (rubber components) such as olefin elastomers and styrene elastomers. These optional components may be used in combination of two or more kinds.

[0065] <Method of manufacturing stampable sheet> The stampable sheet of the present invention is preferably produced by impregnating a mat made of glass fibers (hereinafter, sometimes referred to as a "glass fiber mat") with the above-mentioned present resin composition, although the production method thereof is not particularly limited. That is, the stampable sheet of the present invention preferably includes a mat obtained by impregnating glass fibers with the resin composition of the present invention. Methods of impregnation include a method of applying the above-mentioned resin composition to a glass fiber mat, a method of preparing a sheet of the resin composition (hereinafter sometimes referred to as a "resin sheet"), laminating the resin sheet on the glass fiber mat, and heating and melting the resin sheet to impregnate the mat. In the present invention, from the viewpoint of the impregnation of the resin into the fibers, a method of laminating a resin sheet on a glass fiber mat and heating and melting it is preferable. In particular, the glass fiber mat is laminated between two resin sheets, and then the laminate is heated and pressurized, and then cooled and solidified to obtain the laminate. The thickness of the resin sheet is not particularly limited as long as it allows good impregnation of the glass fiber mat.

[0066] (fiberglass mat) The form of the glass fiber is not particularly limited, and various forms can be used, but a mat or sheet is preferable, and more specifically, a mat (glass fiber mat) formed from glass fiber is preferable. Examples of the form of the glass fiber mat used in the present invention include felt and blankets processed with short fiber glass wool, chopped strand mats processed from continuous glass fibers, swirl (spiral) mats of continuous glass fibers, and unidirectionally aligned mats. Among these, the use of a glass fiber mat obtained by needle punching a swirl (spiral) mat of continuous glass fibers is particularly preferable, since the stampable sheet has excellent strength and impact resistance.

[0067] The basis weight (mass per unit area) of the glass fiber mat is not particularly limited and is determined appropriately depending on the application, but is preferably 300 g / m 2 More preferably, 800 g / m 2 More preferably, 1500 g / m 2 The basis weight of the glass fiber mat is not particularly limited, but is preferably 5000 g / m 2 Less than 4500g / m 2 Less than 4000g / m 2 Less than 3500 g / m 2 The following is the result.

[0068] The basis weight per unit area of ​​the glass fiber mat can be set within the above range by adjusting the amount of fiber per unit area when the glass fiber aggregates constituting the glass fiber mat are laminated by a folding device. The glass fiber mat of the present invention may be a structure in which a plurality of glass fiber mats are bonded together, or a single structure, but a single structure is preferable from the viewpoints of handling properties and peel strength at the bonding interface.

[0069] In the method of laminating a resin sheet on a glass fiber mat and heating and melting the resin sheet, the heating temperature is preferably 170 to 300° C. If the heating temperature is 170° C. or higher, the flowability of the thermoplastic resin (A) such as a polypropylene resin is sufficient, and the glass fiber mat can be sufficiently impregnated with the resin composition, thereby obtaining a suitable stampable sheet. On the other hand, if the heating temperature is 300° C. or lower, the resin composition does not deteriorate. Furthermore, the pressure applied is preferably 0.1 to 1 MPa. When the pressure applied is 0.1 MPa or more, the glass fiber mat can be sufficiently impregnated with the resin composition, and a suitable stampable sheet can be obtained. On the other hand, when the pressure is 1 MPa or less, the resin composition flows and no burrs are generated. The cooling temperature is not particularly limited as long as it is equal to or lower than the solidification point of the thermoplastic resin (A) in the resin composition, but if the cooling temperature is equal to or lower than 80° C., the stampable sheet obtained will not deform when it is taken out. From the above viewpoints, the cooling temperature is preferably from room temperature to 80° C.

[0070] Methods for obtaining a stampable sheet by heating, pressurizing, and cooling the above-mentioned laminate include a method of press-molding the laminate in a mold equipped with a heating device, and a lamination process in which the laminate is heated and pressurized by passing it between two pairs of rollers equipped with a heating device. In particular, the lamination process is preferred because it has good productivity as it allows continuous production.

[0071] <Thickness of stampable sheet> The thickness of the stampable sheet of the present invention is usually 1 to 10 mm, preferably 2 to 5 mm. When the thickness of the stampable sheet is 1 mm or more, the stampable sheet is easy to produce, while when the thickness of the stampable sheet is 10 mm or less, long-term preheating is not required when processing the stampable sheet by stamping molding or the like, and good molding processability is obtained.

[0072] <Molded body> The stampable sheet of the present invention can be molded into a desired shape by stamping in a conventional manner to obtain a molded article made of the stampable sheet.

[0073] <Application> Examples of applications of the stampable sheet of the present invention include various parts in the industrial field, such as automobile parts and electrical and electronic equipment parts. In particular, since it has excellent strength, rigidity, and conductivity, and is also excellent in processability, it can be suitably used for applications that require a good balance of these performances, such as various housings and cases such as battery cases. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0075] [Evaluation method] A stampable sheet was formed from the resin composition of the present invention, and the stampable sheet was evaluated by the following method. 1. Electromagnetic wave shielding property The stampable sheets obtained in the examples and comparative examples were evaluated by the KEC method using an electromagnetic wave shielding effect measuring device developed by the Kansai Electronics Industry Development Center, a general incorporated association. An electromagnetic wave with a frequency of 1.7 MHz was used. The measurement was performed in an atmosphere with a temperature of 25°C and a relative humidity of 30 to 50%.

[0076] 2. Processability The processability was evaluated as follows. First, three stampable sheets of 120mm x 230mm x 3.8mm were stacked and heated to 230℃ with an infrared heater. The mold temperature was 45℃ and the molding pressure was 190kg / cm. 2 The sample was press-molded under the above conditions to be processed into a box-shaped molded product of 300 mm x 180 mm x 3 mm x 65 mm, and then visually evaluated according to the following evaluation criteria. A (◯): The polypropylene resin composition is filled up to the ends of the molded article. B(x): The polypropylene resin composition is not filled up to the ends of the molded article.

[0077] (Materials used) 1. Polypropylene resin (thermoplastic resin (A)) "Novatec PP" (melt flow rate: 60 g / 10 min) manufactured by Japan Polypropylene Corporation was used.

[0078] 2. Phosphorus-based flame retardants (B) A phosphorus-based flame retardant composition (ADEKA CORPORATION, Adeka STAB FP-2500S, an intumescent flame retardant containing 50 to 60 mass% piperazine pyrophosphate, 35 to 45 mass% melamine pyrophosphate, and 3 to 6 mass% zinc oxide relative to the total mass of the phosphorus-based flame retardant composition) was used.

[0079] 3. Coke powder (C) Finely ground pitch coke manufactured by Seachem was used.

[0080] 4. Carbon fiber (C) Mitsubishi Chemical carbon fiber pellets "Pyrofil Pellet PP-C-30A" were used.

[0081] 5. Dispersant (D) An α-olefin-maleic anhydride copolymer (Diacarna 30M, weight average molecular weight 7,800, manufactured by Mitsubishi Chemical Corporation) was used.

[0082] 6. Fiberglass mat A swirl mat (basis weight 890 g / m) made from continuous glass fibers (fiber diameter 23 μm) of roving 2 ) was used as a needle punched glass fiber mat.

[0083] Preparation Example 1 (Preparation of Resin Composition) The above polypropylene-based resin, phosphorus-based flame retardant, coke powder, carbon fiber and dispersant were dry-blended in amounts of 52.25 mass%, 30 mass%, 15 mass%, 2 mass% and 0.75 mass%, respectively, to prepare pellets of a polypropylene-based resin composition (hereinafter sometimes referred to as "PP composition 1").

[0084] Comparative Preparation Example 1 (Preparation of Resin Composition) A resin composition was obtained in the same manner as in Preparation Example 1, except that no dispersant was used. Specifically, the polypropylene resin, phosphorus-based flame retardant, coke powder, and carbon fiber were dry-blended in amounts of 53 mass%, 30 mass%, 15 mass%, and 2 mass%, respectively, to prepare pellets of a polypropylene resin composition (hereinafter, sometimes referred to as "PP composition 2").

[0085] Example 1 The pellets of the PP composition 1 granulated in Preparation Example 1 were put into an extruder, melted, and then extruded into a sheet shape, and the extruded sheet-shaped PP composition (hereinafter referred to as "PP sheet") and the glass fiber mat were laminated in a mass ratio of 67:34, with the PP sheet as the outermost layer and the glass fiber mat being supplied between them, and then heated and pressed at 230°C for 4 minutes while applying a pressure of 1.2 MPa using a laminator, and then cooled and solidified to obtain a stampable sheet (thickness: 3.8 mm). The PP sheet was impregnated into the glass mat fiber, and an integrated stampable sheet was obtained. The results of the evaluation by the above method are shown in Table 1.

[0086] Comparative Example 1 A stampable sheet was produced in the same manner as in Example 1 except that PP composition 2 was used instead of PP composition 1 in Example 1, and was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0087] [Table 1]

[0088] As shown in Table 1, the stampable sheet of Example 1 exhibits excellent electromagnetic wave shielding properties and is also excellent in processability. In particular, it is clear that the electromagnetic wave shielding properties are improved compared to the stampable sheet of Comparative Example 1 that does not contain a dispersant. [Industrial Applicability]

[0089] The stampable sheet of the present invention is useful as a material for various industrial parts that require high safety, such as aircraft, ships, automobile parts, electrical and electronic equipment parts, building materials, etc. In particular, it can be suitably used for various battery housings and cases that have traditionally been made of metal, and is expected to contribute to the safety of automobiles as well as improve energy efficiency and reduce CO2 emissions by reducing weight. In addition, when the stampable sheet of the present invention is used for a battery housing, the main component is resin, so that the processability is excellent. Moreover, since the battery housing is lightweight, the structure using the battery housing is useful as an electric mobility. Furthermore, since the stampable sheet of the present invention has excellent electromagnetic wave shielding properties, in the automotive field, it can block unnecessary electromagnetic waves with high precision for accurate sensing of distance, speed, and obstacle sensing technologies that use electromagnetic waves. The resin composition of the present invention, which is thus useful, and the stampable sheet obtained from the resin composition are extremely useful industrially and are considered to have high technical value.

Claims

1. The present invention comprises a thermoplastic resin (A), a phosphorus-based flame retardant (B), coke powder and / or carbon fiber (C), and a dispersant (D), The resin composition, wherein the dispersant (D) comprises an acid-modified polyolefin resin.

2. The resin composition according to claim 1 , wherein the phosphorus-based flame retardant (B) comprises a compound having a melamine structure or a piperazine structure.

3. The resin composition according to claim 1 , wherein the phosphorus-based flame retardant (B) comprises an intumescent flame retardant.

4. The resin composition according to claim 1, wherein the dispersant (D) comprises a copolymer of an α-olefin and an unsaturated carboxylic acid.

5. The resin composition according to claim 4, wherein the unsaturated carboxylic acid is maleic anhydride.

6. The resin composition according to claim 1 , wherein the thermoplastic resin (A) comprises a polypropylene resin.

7. A stampable sheet comprising the resin composition according to any one of claims 1 to 6 and glass fibers.

8. The stampable sheet according to claim 7 , comprising a mat formed by impregnating the glass fibers with the resin composition.

9. The stampable sheet according to claim 8 , wherein the mat is a glass fiber mat produced by needle punching a swirl mat of continuous glass fibers, and impregnated with the resin composition.

Citation Information

Patent Citations

  • Conductive resin composition and electromagnetic wave shield material using the composition

    JP1994251620A

  • Glass filament-containing flame-retardant resin composition and molded article

    JP2011088970A

  • Flame-retardant polyolefin resin composition

    JP2013119575A

  • Battery case for vehicle

    JP2014062189A

Cited By

  • High flame-retardant product, method for manufacturing the same, and high flame-retardant long-fiber polypropylene composite material thereof

    JP2026121335A